Pengaruh Kepemimpinan Terhadap Kepuasan Kerja Guru Pada SMK Muda Pekanbaru - Yayang, Yayang; iskandar, iskandar (Eko dan Bisnis: Riau Economic and Business Review, 2025)
The objective of this study is to examine The Influence of Leadership on Teacher Job Satisfaction at SMK MUDA Pekanbaru. The research population consisted of all teachers at SMK MUDA Pekanbaru during the 2023/2024 academic year, totaling 60 individuals. The research sample comprised 59 respondents. The research methodology employed in this study utilized descriptive and quantitative methods, subsequently analyzed using simple linear regression analysis. The descriptive data analysis results revealed that the mean value for the Leadership variable was 3.94, indicating that respondents' answers to all Leadership statements were categorized as "Agree" (favorable). Based on the regression analysis results, it was found that the calculated t-value exceeded the table t-value (7.871 > 2.002) with a significance level of less than 0.05 (0.000 < 0.05), therefore Ha was accepted. This indicates that Leadership has a positive and significant influence on Teacher Job Satisfaction at SMK MUDA Pekanbaru. The R-square value obtained was 0.521 or 52.1%, meaning that Leadership has a 52.1% influence on Teacher Job Satisfaction at SMK MUDA Pekanbaru, while the remaining 47.9% (100-52.1) is influenced by other variables not examined in this study.